Acknowledging awareness: informing families of individual research results for patients in the vegetative state - Graham, Mackenzie (J Med Ethics, 2015)
Recent findings in cognitive neuroscience have revealed that some patients previously diagnosed as being in a vegetative state may retain some degree of covert awareness. However, it is unclear whether such findings should be disclosed to the families of these patients. Concerns about the preservation of scientific validity, reliability of results and potential harms associated with disclosure suggest that individual research results should be disclosed only under certain conditions. In the following paper, we offer four criteria for the disclosure of individual research results. Because the results of functional neuroimaging studies to detect covert awareness in vegetative patients are scientifically valid, informative and reasonably reliable and have considerable potential benefit for the patient, researchers have an obligation to disclose such results to family members. Further work is needed to develop educational materials for families and to systematically study the impact of disclosure on the families themselves.